Current problems on the development and relevance of the thought of Rodrigo Facio Brenes - Esquivel Villegas, Francisco (2020)
The development of open economies needs the complementarity of the external market with the internal dynamics of the productive apparatus. The economic expansion of Costa Rica from the mid-nineteenth century to the 1930s revealed the limitations of a strategy that was based on the predominance of export growth without establishing the appropriate mechanisms to stimulate the domestic market. The analysis of Rodrigo Facio Brenes, formulated at the beginning of the 1940s, made significant contributions to the definition of an alternative strategy that was put into practice thanks to a period of progressive political transformation. In this regard, the growth of Costa Rica from the mid-twentieth century to the 1970s surpassed the traditional mono-product export model. The global crisis of the 1970s produced productive stagnation and high inflation in the major international markets, affecting the operation of the alternative strategy applied by Costa Rica. This led to a new exporting stage commencing in the late 1980s. However, the strategy that guided this new stage deteriorated the complementarity of the export process with the internal dynamics of the economy. Significant growth occurred, without however generating the appropriate stimulus for the internal market. Accordingly, a review of the export strategy is necessary to restore the appropriate interrelationship betweenthe external and internal sectors of the economy. For this reason, the strategic definitions of Facio continue to be relevant, although the operational context is different from that of the time he lived through.